2016
DOI: 10.1038/cdd.2015.165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling reveals primary mesothelioma cell lines recapitulate human disease

Abstract: Malignant mesothelioma (MM) is an aggressive, fatal tumor strongly associated with asbestos exposure. There is an urgent need to improve MM patient outcomes and this requires functionally validated pre-clinical models. Mesothelioma-derived cell lines provide an essential and relatively robust tool and remain among the most widely used systems for candidate drug evaluation. Although a number of cell lines are commercially available, a detailed comparison of these commercial lines with freshly derived primary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 47 publications
4
64
0
Order By: Relevance
“…The advantages and limitations of the mesothelioma preclinical models are presented in Table 1. (62,67,68). One study discussed the limits of these cell models.…”
Section: Preclinical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages and limitations of the mesothelioma preclinical models are presented in Table 1. (62,67,68). One study discussed the limits of these cell models.…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…One study discussed the limits of these cell models. The authors found strong molecular differences between primary and commercial cell lines (67), mainly due to a high number of divisions after their establishment, and thus an increased risk of new karyotypic changes. These models remain interesting for screening and preliminary investigations.…”
Section: Preclinical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In preclinical models of primary or commercially available MPM cell lines, transcriptome and metabolic profiles have been found to be highly variable. 10 Marked genomic instability was observed from MPM tissue, and the interpatient variability was confirmed by the observation of multiple p53 isoforms in primary cell lines established from MPM tissue. These findings are consistent with the tumor protein p53 gene (TP53) being rarely inactivated in MPM.…”
Section: Introductionmentioning
confidence: 90%
“…This trial stresses the need for in vitro drug testing conditions that reflect genuine mesothelioma tumors more accurately. Primary mesothelioma cultures may provide a valuable model for personalized drug selection for patients with mesothelioma because they recapitulate the original tumor far more accurately than long-established MPM cell lines (21,22).…”
Section: Introductionmentioning
confidence: 99%